Breaking the Cycle: School Leadership in Action for Creating a Bully-Free Learning Environment - Mokoena, Mkhulu David; Letuma, Motsekiso Calvin; Makhasane, Sekitla Daniel (Studies in Learning and Teaching, 2025)
Bullying remains a persistent challenge, affecting both students and the overall school environment. Enhancing the school management team’s (SMT) capacity to address this issue helps create safer, more supportive environments that foster quality education, aligning with the fourth Sustainable Development Goal. This study explores strategies to enhance the leadership practices of SMT in addressing bullying in South African secondary schools. The study adopted an interpretative paradigm and a qualitative approach, with a multiple case study design. Three secondary schools and nine SMT members were selected using purposive sampling. Data was collected using semi-structured interviews and was analyzed thematically. The findings highlight several key areas for improvement. Professional development through workshops was identified as a crucial method for equipping SMT with the knowledge and skills to tackle bullying. The study also found that collaboration with external stakeholders, including the Department of Inclusive Education, the South African Police Service, correctional services, and Non-Governmental Organizations, is essential to provide a holistic response to bullying. Additionally, the study suggests that district-based support teams should broaden their scope, shifting from only curriculum-related matters to social challenges like bullying. Furthermore, integrating bullying prevention into the Life Orientation curriculum was recommended to raise awareness and equip students with the skills to prevent bullying. The study recommends regular training, greater collaboration, and curriculum reforms to foster a bullying-free school culture. The study concludes that a distributed leadership approach, where responsibility is shared among SMTs, external stakeholders, and the district, is essential for creating an environment where bullying can be managed.